Serum gangliosides in mice with metastatic and non-metastatic brain tumors. - M Cotterchio; T N Seyfried (Journal of Lipid Research, 1994)
The content of serum gangliosides was examined in VM and C57BL/6J (B6) mice that contained subcutaneous metastatic (VM) and non-metastatic (CT-2A) brain tumors, respectively. Gas-liquid chromatography (GLC) and high performance thin-layer chromatography (HPTLC) were used to analyze the serum gangliosides. N-glycolylneuraminic acid (NeuGc) accounted for greater than 90% of the total serum sialic acid content in each mouse strain (5.53 nmol and 2.05 nmol per ml serum, respectively). GM2-NeuGc was the major serum ganglioside detectable in both the normal and tumor-bearing mice of each strain. Shedding of tumor gangliosides into the serum occurs in various murine non-neural tumors and in human gliomas and neuroblastomas, but has not been previously studied in murine brain tumors. Our results show that serum ganglioside concentration was reduced in VM mice bearing the metastatic VM tumor, but was increased in B6 mice bearing the non-metastatic CT-2A tumor. These changes in concentration, however, were not associated with marked changes in serum ganglioside distribution. As serum gangliosides are synthesized in the liver, the differences in serum ganglioside concentration in the tumor-bearing mice may arise more from changes in liver function than from differences in tumor shedding.